Strain-induced effects in advanced MOSFETs - Sverdlov, Viktor (Computational microelectronics, 2011)
Strain is used to boost performance of MOSFETs. Modeling of strain effects on transport is an important task of modern simulation tools required for device design. The book covers all relevant modeling approaches used to describe strain in silicon. The subband structure in stressed semiconductor films is investigated in devices using analytical k.p and numerical pseudopotential methods. A rigorous overview of transport modeling in strained devices is given